Feeling Manipulated: How Tip Request Sequence Impacts Customers and Service Providers?. (February 2021) - Warren, Nathan; Hanson, Sara; Yuan, Hong
Technology is changing frontline service scripts. Businesses are now using mobile point-of-sale applications (e.g., Square) and mobile technology (e.g., iPad) to prompt customers for tips. Tip requests are occurring more frequently at the start of service transactions, before any service has been provided. This research examines how requesting a tip either before or after service completion affects customers and service providers. We test the effects of preservice versus postservice tip sequence in four studies (a natural experiment in the field and three controlled experiments) across food and beauty service contexts. Findings reveal that requesting a tip before (vs. after) completing a service leads to smaller tips, reduced return intentions, diminished word-of-mouth intentions, and lower online ratings. Inferred manipulative intent is revealed as the psychological mechanism underlying the harmful effects of requesting a tip before service. Findings suggest that emphasizing the benefits of automated point-of-sale systems can reduce, but not eliminate, the negative effects of preservice tip requests. Contrary to norms within the service industry, we find that service providers should avoid requesting tips before serving customers.